PERAN SEKTOR INFORMAL TERHADAP PEREKONOMIAN DAERAH: PENDEKATAN DELPHI-IO DAN APLIKASI - Widodo, Tri (Journal of Indonesian Economy and Business, 2006)
This paper analyzes theoritically and empirically the role of informal sectors onthe local economic development. In general, the local governments do not put theinformal sectors as a focus of the local economic development. Regular data collectionregarding to the informal sectors is almost unavailable. This paper derives a method inanalysing the role of the informal sectors in local economy by combining quantitative(non survey) and qualitative (survey) method. Input-Output (IO) Table analysis isapplied. Survey (Delphi method) is conducted to get the information about thecontribution of the informal sectors. This information is used to derive the Input-OuputTable (IO*) which put into account the role of the informal sectors. Therefore, someparameters (multipliers and linkages) calculated from IO and IO* are compared. Thispaper applies the method to look at Daerah Istimewa Yogyakarta (DIY) as a case study.Some conclusions are withdrawn in the case of DIY: first, the informal sectors give apositive contribution to local economic development in terms of output, income,employment and sectoral linkages. Second, the role of informal sectors has to be limmitedin some certain level.Keywords: Informal sectors; Input-Output Analysis; Delphi Method